PELAKSANAAN PEMBINAAN NARAPIDANA WANITA PELAKU TINDAK PIDANA NARKOTIKA DI RUTAN WANITA KELAS II A SURABAYA - Prabowo, Muhammad Juniar; Kartika, Adhitya Widya (Universitas Ekasakti, 2023)
This study aimed to find out the coaching exercises for women perpetrators of narcotics crimes in Class II A Women's Detention Centers in Surabaya. This study uses empirical juridical research methods. Data analysis used is a qualitative approach to primary and secondary data. The results of research on narcotics women's psychoactive psychotherapy training at Class II A Women's Detention Center in Surabaya concluded that Class II A Surabaya Women's Detention Center carried out 2 (two) training programs for female psychopaths. The first is personality development where this coaching is more directed to the personality of each person with disabilities, this coaching itself includes spiritual development and physical training. The second is self-reliance coaching where this training is so that when the tired ones leave the Surabaya Class II A Women's Detention Center they can become even more independent with the provision of coaching results at the Class II A Women's Detention Center Surabaya.